Relaxation of Purifying Selection on Live Attenuated Vaccine Strains of the Family Paxamyxoviridae - Hughes, Austin L. (2009)
In wild-type sequences of three paramyxoviruses (measles virus, mumps virus, and Newcastle disease virus), nucleotide diversity at both non-coding sites and at nonsynonymous sites in coding regions was significantly reduced in comparison to that at synonymous sites. Likewise, both the mean and variance of gene diversity at nonsynonymous polymorphic sites were reduced in comparison to non-coding and synonymous sites. Neither of these patterns, which reflect the action of purifying selection against deleterious mutations at nonsynonymous and non-coding sites, was seen in the case of live attenuated vaccine strains, implying that purifying selection has been substantially relaxed on the latter, potentially affecting their biological properties, including antigenicity and vaccine effectiveness. Since the accumulation of mutations increases as s a function of the number of generations of replication, these findings highlight the utility of minimizing the number of generations between the original vaccine master seed and the strains used in vaccination, along with periodic monitoring of the extent of sequence evolution.